NURSING'S RELATIONSHIP WITH MEDICATION ERRORS: AN INTEGRATIVE REVIEW - Elaine Cristina Novatzki Forte; Francele Luz Machado; Denise Elvira Pires de Pires (Universidade Federal do Paraná, 2016)
This integrative review aimed to identify in the literature the relationship between medication errors and the nursing team. The study was undertaken by two independent collaborators, in three databases, in the period 2011 - 2015, with 32 studies. The results were divided in two macrocategories: characteristics of the studies, and the direct and indirect relationships between nursing and the medication errors. The direct relationships refer to issues of the professional ambit, such as lack of knowledge and of experience, failures in communication, stress and the distraction of the professionals. The indirect relationships are made up of issues related to prescribing and dispensing, the patient's physical conditions, and errors in the production of the medications. It is concluded that, besides the nursing staff working in administering medications with a view to safe care for the patient, they can act as a barrier to errors arising from other phases of the medication process.